Influence of American Society of Anesthesiologists Score on Oncologic Outcomes in Patients With Upper Tract Urothelial Carcinoma After Radical Nephroureterectomy: A Large-Sample Study in Two Institutions - Yuan, Yichu; Wang, Yiqiu; Zhang, Nan; Mao, Xiawa; Huang, Yiran; Huang, Jiwei; Ji, Na (Frontiers in Oncology, 2021)
Abstract: Introduction: Accurate risk assessment are particularly important for patients being considered for surgery. we sought to investigate the prognostic significance of American Society of Anesthesiologists (ASA) score in patients with upper tract urothelial carcinoma (UTUC) after radical nephroureterectomy (RNU). Methods: A review was performed on 958 patients with UTUC from January 1998 to June 2019 who underwent RNU at two Chinese institutions retrospectively. The ASA scores were obtained from anesthesia chart. Clinical and pathologic variables were assessed. Overall survival (OS), cancer-specific survival (CSS), intravesical recurrence-free survival (IRFS) and metastatic-free survival (MFS) were estimated using the Kaplan-Meier method and Cox regression analyses. Results: In our study, the median follow-up time for all patients was 39 months. The group of patients with ASA=2/3 had a shorter 5-year OS (67.6% and 49.9%), CSS (72.9% and 58.1%) and MFS (75.1% and 58.5%). Kaplan-Meier curves showed that group with ASA=2/3 had significantly poor OS, CSS and MFS. Multivariate analyses suggested that ASA score was an independent predictor of OS, CSS and MFS (P=0.004, 0.005, <0.001). Conclusion: Significantly, higher ASA scores was independently associated with lower survival rate. This strong predictor of morbidity should be seriously referenced in patients being considered for RNU.